Rising Strong: Does Personal Resilience Drive Civic Engagement During Disasters? - Efrat Blitstein-Mishor (Emergency Care and Medicine)
Background: In the crucible of disasters, civic engagement emerges as a dynamic force that channels individual strength and collective willpower toward the common good. Although it has been recognized as a necessary precondition for community resilience, studies on the motivators for citizens’ activities during disasters are relatively limited. This study underscores the interplay of personal resilience, risk perception, and coping strategies in the context of emergency-oriented civic engagement. It provides a robust framework for comprehending the cognitive and emotional processes that drive individuals’ responses to threats and risks to improve knowledge about public behavior, psychological conditions, and mental health during man-made disasters. Method: an online survey was conducted with a sample of 1514 citizens in Israel. A model incorporating both moderation and mediation effects was proposed. Results: The results reveal a consistent positive relationship between personal resilience and emergency-oriented civic engagement and point to the importance of both the intervening role of risk perception and the moderating role of coping strategies. Conclusions: discuss the importance of resilience-building programs and the promotion of positive coping strategies which can empower individuals to navigate the complexities of risk perception and engage actively in civic activities during disasters.